ENGLISH-INDONESIAN SLANG (ALAY): AN ETHNOGRAPHY STUDY - Okta Mahendra (Universitas Ahmad Dahlan)
English is absolutely crusial International language having function as one of global communication tools to connect one country to another countryOne can not be ignored that in Indonesia, English is not only International language but also expanding language influencing the citizens to mix Bahasa Indonesia and English as the slang. Nowadays teenagers use Bahasa Indonesia slang adopted by English words, phrase, and terms. This looks at the society, especially teenagers and the transition from adolescence to adulthood (12 to 23 years). This phenomenon is actually very unique which they use some English words or phrases as their Alay slang language to communicate. It is such a case that should be researched by researcher and many people caring about Bahasa Indonesia and the way English insert in that slang. The cause and the use of it is the main case of that is actually the focus of research.This study uses a qualitative approach design; ethnography research. A qualitative approach design using data derivedfrom documents. While the form of data collecting technique is content analysis of secondary text or visual material where the researcher analyzes the content of the documents grabbed, describe, interprete, determine the settings, last is report reflexively. The data is taken from documents; screenshot of conversations of subjects in Blackberry Messenger with several themes where the English-language Alay language is usually used ie the problem of romance and vacation.